CFD Benchmark Tests for Indoor Environmental Problems: Part 4 Air-conditioning Airflows, Residential Kitchen Airflows and Fire-Induced Flow - Ito, Kazuhide; Kiao Inthavong; Takashi Kurabuchi; Toshikatsu Ueda; Tomoyuki Endo; Toshiaki Omori; Hiroki Ono; Shinsuke Kato; Koji Sakai; Yoshihide Suwa; Hiroshi Matsumoto; Hajime Yoshino; et al. (International Journal of Architectural Engineering Technology, 2015)
Computational Fluid Dynamics (CFD) has become practical design tool for indoor environment recent years and the application cases have been increasing. Though the improvement of the prediction accuracy of CFD is needed in connection with the upgrade of design quality in indoor environment and Heating, Ventilation and air-conditioning (HVAC) system, the prediction accuracy of CFD simulation depends on the understanding for the fundamentals of fluid dynamics and the setting of appropriate boundary and numerical conditions as well. Additionally, deeper understanding to a specific problem regarding indoor environment is also required. The series of this study aimed to provide with the practical information such as prediction accuracy and problematic areas related to CFD applications in air conditioning and ventilation, then performed benchmark tests and reported the results. Especially in this Part 4, benchmark test results for Air-conditioning airflows, Residential kitchen airflows and Fire-induced flow were introduced and discussed.